Multivariable Analysis of Wasting Incidents in Children Under the Age of 5 in Kupang Regency - Yosefa Sarlince Atok; Maria Vilastry Nuhan; Roslin Evelin Margareth Sormin; Damita Palalangan (Universitas Islam Negeri Sumatera Utara, Medan, 2023)
Wasting is the condition of a child whose weight decreases over time until the total body weight is far below the standard growth curve or weight for height is low (thin) and shows weight loss (acute) and is severe. East Nusa Tenggara, the frequency of acute and chronic nutrition ranks highest in Indonesia with the prevalence of wasting still above the national average. The prevalence of wasting in NTT will increase from 7.5% in 2021 to 8.0% in 2022. Kupang Regency is one of the districts in NTT that experienced the highest increase in the percentage of wasting under five, namely 11 % and in absolute terms under five with wasting nutrition problems 42 under five in Year 2021 (NTT Provincial Health Office, 2021). This research is an observational analytic study. The approach is carried out by case control and using a multivariable model which is one of the analytical techniques to determine the relationship between various variables in health. The research will be carried out using simple random sampling. Kupang Regency is one of the districts in NTT that experienced the highest increase in the percentage of wasting under five, namely 11 % and in absolute terms under five with wasting nutrition problems 42 under five in Year 2021 (NTT Provincial Health Office, 2021). The results of this study indicate that the factors causing wasting are exclusive breastfeeding (41.9%), Basic Sanitation (56.3%), Parenting (88.2%), and Parents Income (42.9%). The results of this study indicate that the causes of wasting based on these variables have a significant difference (p <0.05). Recommendations from this study are expected for policy makers both in health services to carry out socialization and counseling about exclusive breastfeeding, parenting, sanitation and parents income. Keyword: Basic sanitation, Exclusive breastfeeding, Parenting, Parents income, Wasting